Minimizing the Energy Consumption in Wireless Sensor Networks (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Energy in Wireless Sensor networks (WSNs) represents an essential factor in designing, controlling and operating the sensor networks. Minimizing the consumed energy in WSNs application is a crucial issue for the network effectiveness and efficiency in terms of lifetime, cost and operation. Number of algorithms and protocols were proposed and implemented to decrease the energy consumption. Principally, WSNs operate with battery-powered sensors. Since Sensor's batteries have not been easily recharge.  Therefore, prediction of the WSN represents a significant concern. Basically, the network failure occurs due to the inefficient sensor's energy. MAC protocols in WSNs achieved low duty-cycle by employing periodic sleep and wakeup. Predictive Wakeup MAC (PW-MAC) protocol was made use of the asynchronous duty cycling. It reduces the consumption of the node energy by allowing the senders to predict the receiver′s wakeup time. The WSN must be applied in an efficient manner to utilize the sensor nodes and their energy to ensure effective network throughput. To ensure energy efficiency the sensors' duty cycles must be adjusted appropriately to meet the network traffic demands. The energy consumed in each node due to its switching between the active and idle states was also estimated. The sensors are assumed to be randomly deployed. This paper aims to improve the randomly deployed network lifetime by scheduling the effects of transmission, reception and sleep states on the energy consumption of the sensor nodes. Results for these states with much performance metrics were also studied and discussed.